Uncertainty Feasible Region Analysis for Microgrids in the Coordination with Distribution System Considering Interactive Power Deviation - Hao Dong; Peng Lu; Xiang Jiang; Xu Chen; Puyan Wang; Junpeng Zhu (Algorithms)
The coordination of microgrid (MG) and distribution is an emerging trend for future development. This paper proposes an uncertainty feasible region (UFR) analysis method based on outer approximation cutting (OAC) under the coordination of MG and distribution. Firstly, an optimal economic dispatch scheduling is obtained. It serves as the basis for the intraday analysis of UFR. Drawing on the concepts of robust optimization, a method for determining the intra-day UFR is proposed. Subsequently, the problem is transformed using duality theory by identifying umbrella constraints, ultimately linearizing the problem to enable its solution by commercial software. In the intra-day analysis of the feasible region, the interactive power deviation between the MG and the upper-level grid (ULG) is allowed, which is represented by an interactive power deviation factor (IPDF). Different factors represent varying sizes of controllable resources, and a larger factor positively affects the size of the feasible region, and the volume is used to represent the size of the feasible region. The UFR defined in this paper provides a theoretical basis for renewable energy consumption capacity corresponding to the day-ahead dispatch scheduling. The effectiveness of the proposed method is validated by simulation results in a typical MG scenario.